Development of HoTS-Based Elementary Linear Algebra Course Test Instruments Charged With Islamic Character - Andi Ika Prasasti Abrar; Andi Kusumayanti (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
This test is known as an evaluation tool or test instrument in the form of questions that are prepared in accordance with learning indicators. A lecturer should be able to provide questions that can trigger students to think at a higher level so that they can be more optimal in achieving learning objectives. This study aims to produce HOTS-based test instruments with Islamic characters by looking at the development procedures and quality of HOTS-based test instruments with Islamic characters developed. The type of development used is research research and development (RD), namely the development of test instruments for linear algebra courses. The development model used is a formative research (Tessmer) model which goes through 4 stages, namely preliminary, self-evaluation, prototyping (expert review, one to one, small group), and field test. The test subjects in this study were students of mathematics education class PMAT B, Faculty of Tarbiyah and Teacher Training, UIN Alauddin Makassar with a total of 33 students. Based on the results of the trials conducted, it was obtained that: (1) the test instrument was declared "valid" with a very suitable category, the test instrument was declared reliable with a very high category (reliable), the test instrument had a fairly good difficulty level with a moderate category, the test instrument had a good distinguishing power with a good category. Thus, the test instruments of the HOTS-based elementary linear algebra course with Islamic characters are of good quality. Therefore, HOTS-based test instruments with Islamic characters can be used as evaluation tools in the form of exercises, quizzes, and semester exams to measure students' higher order thinking skills.Tes ini dikenal dengan istilah alat evaluasi atau instrumen tes berupa soal-soal yang disusun sesuai dengan indikator pembelajaran. Seorang dosen hendaknya mampu memberikan soal-soal yang dapat memicu mahasiswa untuk berpikir tingkat tinggi agar dapat lebih optimal dalam mencapai tujuan pembelajaran. Penelitian ini bertujuan menghasilkan instrumen tes berbasis HOTS bermuatan karakter islami dengan melihat prosedur pengembangan dan kualitas instrumen tes berbasis HOTS bermuatan karakter islami yang dikembangkan. Jenis pengembangan yang digunakan ada-lah penelitian research and development (RD) yaitu pengembangan instrumen tes mata kuliah aljabar linear. Model pengembangan yang digunakan adalah model formative research (Tessmer) yang melalui 4 tahap yaitu preliminary, self evaluation, prototyping (expert review, one to one, small group), dan field test. Subjek uji coba pada penelitian ini adalah mahasiswa pendidikan matematika kelas PMAT B, Fakultas Tarbiyah dan Keguruan, UIN Alauddin Makassar dengan jumlah 33 mahasiswa.. Berdasarkan hasil uji coba yang dilakukan, diperoleh bahwa: (1) instrumen tes dinyatakan “valid” dengan kategori sangat sesuai, instrumen tes dinyatakan reliabel dengan kategori sangat tinggi (reliabel), instrumen tes memiliki tingkat kesukaran yang cukup baik dengan kategori sedang, instrumen tes memiliki daya pembeda yang baik dengan kategori baik. Dengan demikian, instrumen tes mata kuliah aljabar linear elementer berbasis HOTS bermuatan karakter islami memiliki kualitas yang baik. . Oleh karena itu, Instrumen tes berbasis HOTS bermuatan karakter islami dapat digunakan sebagai alat evaluasi berupa latihan, kuis, dan ujian semester untuk mengukur kemampuan berpikir tingkat tinggi mahasiswa.